The risk of Ascaris lumbricoides infection in children as an environmental health indicator to guide preventive activities in Caparaó and Alto Caparaó, Brazil - Carneiro Fernando Ferreira; Cifuentes Enrique; Tellez-Rojo Martha Maria; Romieu Isabelle (The World Health Organization, 2002)
OBJECTIVE: To develop an environmental health indicator for use as a basis for developing preventive measures against Ascaris lumbricoides infection in children from the rural municipalities of Caparaó and Alto Caparaó, in Minas Gerais, Brazil. METHODS: A cross-sectional survey was conducted between May and September 1998 among 1171 children under 14 years of age living in 588 dwellings selected from 11 communities. Trained interviewers used a questionnaire to identify risk factors for infection (socioeconomic, sanitation and hygiene variables) and collected stool samples from each child for parasitological tests. RESULTS: The overall prevalence of A. lumbricoides infection was 12.2%. The results showed the protective effects of availability of water in the washbasin and better hygiene, sanitation and socioeconomic status; the interactive effect of crowding was five times larger in households without water in the washbasin than in those having water. There was a statistically significant association between infection and children's age. CONCLUSION: The environmental health indicator, which incorporated the most significant biological, environmental and social factors associated with the risk of A. lumbricoides infection in children from these communities, should contribute to the development of surveillance tools and health protection measures in this population.